Transgelin induces dysfunction of fetal endothelial colony-forming cells from gestational diabetic pregnancies - Varberg, Kaela M. (Am J Physiol Cell Physiol, 2018)
Fetal exposure to gestational diabetes mellitus (GDM) predisposes children to future health complications including hypertension and cardiovascular disease. A key mechanism by which these complications occur is through the functional impairment of vascular progenitor cells, including endothelial colony-forming cells (ECFCs). Previously, we showed that fetal ECFCs exposed to GDM have decreased vasculogenic potential and altered gene expression. In this study, we evaluate whether transgelin (TAGLN), which is increased in GDM-exposed ECFCs, contributes to vasculogenic dysfunction. TAGLN is an actin-binding protein involved in the regulation of cytoskeletal rearrangement. We hypothesized that increased TAGLN expression in GDM-exposed fetal ECFCs decreases network formation by impairing cytoskeletal rearrangement resulting in reduced cell migration. To determine if TAGLN is required and/or sufficient to impair ECFC network formation, TAGLN was reduced and overexpressed in ECFCs from GDM and uncomplicated pregnancies, respectively. Decreasing TAGLN expression in GDM-exposed ECFCs improved network formation and stability as well as increased migration. In contrast, overexpressing TAGLN in ECFCs from uncomplicated pregnancies decreased network formation, network stability, migration, and alignment to laminar flow. Overall, these data suggest that increased TAGLN likely contributes to the vasculogenic dysfunction observed in GDM-exposed ECFCs, as it impairs ECFC migration, cell alignment, and network formation. Identifying the molecular mechanisms underlying fetal ECFC dysfunction following GDM exposure is key to ascertain mechanistically the basis for cardiovascular disease predisposition later in life.